Blood Pressure Lowering for the Secondary Prevention of Stroke - Shunsuke Funakoshi; Miki Kawazoe; Kazuhiro Tada; Makiko Abe; Hisatomi Arima; Tianyu Xu; Xiaoxia Fu (Cardiology Discovery)
Abstract. Hypertension is one of the most important modifiable risk factors for stroke, and greater than 50% of all stroke events are estimated to be attributable to elevated blood pressure (BP). Randomized trials and meta-analyses have demonstrated that reducing BP is the most effective and generalizable strategy for preventing recurrent stroke. Based on currently available evidence, BP should be reduced to below 140/90 mmHg in all patients during the chronic post-stroke phase and to below 130/80 mmHg when well-tolerated.